2013
DOI: 10.1002/ptr.4939
|View full text |Cite
|
Sign up to set email alerts
|

A Biochemical and Cellular Approach to Explore the Antiproliferative and Prodifferentiative Activity of Aloe Arborescens Leaf Extract

Abstract: Aloe arborescens Miller, belonging to the Aloe genus (Liliaceae family), is one of the main varieties of Aloe used worldwide. Although less characterized than the commonest Aloe vera, Aloe arborescens is known to be richer in beneficial phytotherapeutic, anticancer, and radio-protective properties. It is commonly used as a pharmaceutical ingredient for its effect in burn treatment and ability to increase skin wound healing properties. However, very few studies have addressed the biological effects of Aloe at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…A previous study by the present authors also indicated that mTORC2 is a target of aloe-emodin, and aloe-emodin can strongly inhibit the AKT activation caused by PTEN loss (36). Aloe-emodin is a natural compound from aloe or Rheum palmatum (39,40). The present study aimed to determine the efficacy of aloe-emodin in the treatment of EC.…”
Section: Introductionmentioning
confidence: 65%
“…A previous study by the present authors also indicated that mTORC2 is a target of aloe-emodin, and aloe-emodin can strongly inhibit the AKT activation caused by PTEN loss (36). Aloe-emodin is a natural compound from aloe or Rheum palmatum (39,40). The present study aimed to determine the efficacy of aloe-emodin in the treatment of EC.…”
Section: Introductionmentioning
confidence: 65%
“…All data were processed with TopSpin. 1 H NMR diffusion experiments were performed using the LED sequence with bipolar gradients [24]. The attenuation measured with this sequence is given by:…”
Section: H Nuclear Magnetic Resonance Analysis and Hydrodinamic Radmentioning
confidence: 99%
“…The spots were selected for mass spectral identification by the merging of images analyses. Proteins excised from the gel were reduced, alkylated, and in situ digested with trypsin as described by Di Luccia et al [23]. The peptide mixtures were analyzed using a CHIP MS 6520 QTOF equipped with a capillary 1200 HPLC system and a chip cube (Agilent Technologies).…”
Section: Composition Of Bioemulsifiermentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, aloe-emodin was not detectable in the leaves of our Aloe arborescens. The concentration of aloin and aloe-emodin may vary among different Aloe species (Hamman 2008;Di Luccia et al 2013). In addition, breeding factors, sampling and post-harvest conditions can play an important role on the chemical characteristics of Aloe homogenates (Wang et al 2010;Lucini et al 2013).…”
Section: Aloe Arborescens Homogenate Compositionmentioning
confidence: 99%